An Analysis of Conversational Structure in Physiotherapist's Medical Consultation at YARSI Padang Panjang - Nur Mukhlisah; Hamzah Hamzah; Fitrawati Fitrawati (Universitas Negeri Padang, 2020)
This research aims to find elements of conversational structures that happen between physiotherapist and his patients at YARSI Padang Panjang when doing medical consultation. This research uses descriptive method to conduct the research. Data of this research are the transcription of recorded conversation that happens during therapy process. The participants who act as the subject of the study and became the source of the data are physiotherapist and his patients at YARSI Padang Panjang.Total patients who do therapy treatment with therapist are 20 patients. From 20 patients, seven of them are new patients, and thirteen of them are regular patients. This research uses Goutsos (2005) theory to analyze elements in global structure of conversation. Meanwhile, Stenstrom (1994) theory uses to analyze the elements of turn-taking systems in local structure of conversation. Result of this research shows that the conversation that happens between physiotherapist and his patients is structured and organized. In global structure section, it is found that every conversation has the elements of opening, body, and closing even though not all elements found in each section. Then, in turn-taking systems case, it is found that three strategies in turn-taking systems found in the research. They are turn-yielding strategy, taking the turn strategy, and turn-holding strategy.